2015
DOI: 10.1093/ndt/gfv346
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomized controlled trial of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker withdrawal in advanced renal disease: the STOP-ACEi trial

Abstract: BackgroundBlood pressure (BP) control and reduction of urinary protein excretion using agents that block the renin–angiotensin aldosterone system are the mainstay of therapy for chronic kidney disease (CKD). Research has confirmed the benefits in mild CKD, but data on angiotensin-converting enzyme inhibitor (ACEi) or angiotensin receptor blocker (ARB) use in advanced CKD are lacking. In the STOP-ACEi trial, we aim to confirm preliminary findings which suggest that withdrawal of ACEi/ARB treatment can stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 44 publications
0
66
0
5
Order By: Relevance
“…One possible explanation is that ACEIs/ARBs may have been discontinued in the late stages of non-dialysis-dependent CKD due to hyperkalemia and concerns about decreased eGFR, and never restarted once the patient transitioned to PD. Indeed, there is an ongoing multicenter randomized controlled trial of ACEI/ARB withdrawal in patients with Stage 4 or 5 CKD that stemmed from such concerns [55]. Clinicians should not shy away from restarting ACEIs/ARBs in incident PD patients since they are much more likely to exhibit hypokalemia than hyperkalemia due to the continuous nature of the dialysis.…”
Section: Table1 Continuedmentioning
confidence: 99%
“…One possible explanation is that ACEIs/ARBs may have been discontinued in the late stages of non-dialysis-dependent CKD due to hyperkalemia and concerns about decreased eGFR, and never restarted once the patient transitioned to PD. Indeed, there is an ongoing multicenter randomized controlled trial of ACEI/ARB withdrawal in patients with Stage 4 or 5 CKD that stemmed from such concerns [55]. Clinicians should not shy away from restarting ACEIs/ARBs in incident PD patients since they are much more likely to exhibit hypokalemia than hyperkalemia due to the continuous nature of the dialysis.…”
Section: Table1 Continuedmentioning
confidence: 99%
“…Some other investigators around the world have shown similar reports raising concerns about the potential nephrotoxicity of angiotensin blockade especially in the elderly (>65-year old) with more advanced CKD (13)(14)(15). As a result of these legitimate concerns, we now have a randomized controlled trial to determine whether the pre-emptive withdrawal of ACEI/ARB in patients with advanced CKD would result in improved cardiorenal outcomes -the ongoing STOP ACEi Trial (16,17). The second case report presented above demonstrated the syndrome of rapid onset ESRD, or SORO-ESRD, that is to say, acute yet irreversible renal failure requiring permanent RRT including kidney transplantation where applicable (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 81%
“…Recent cardiovascular guidelines have recommended caution with the use of ACEi/ARBs for patients with HF and advanced CKD [23]. The potential merits and risks of ACEi/ARB use in advanced CKD is in a state of equipoise and has formed the basis for the current UK-based STOP-ACEi trial, a randomised controlled open label study of ACEi/ARB withdrawal in progressive and advanced CKD [24]. The results of this trial could be critical to delaying the need for expensive and invasive dialysis therapy without being a detriment to other outcomes such as cardiovascular events [25].…”
Section: Uncertainty In the Use Of Acei/arbs In Advanced Ckdmentioning
confidence: 99%
“…Adequately powered randomised control trials to elucidate a potential benefit from cessation of ACEi/ARBs in patients with advanced CKD would be of enormous value to guide optimal clinical practice and delay renal progression and the need for RRT. This has formed the basis for the STOP ACEi trial [24,] but should this apply to all high-risk groups?…”
Section: What Happens To Individuals With Ckd and Proteinuria?mentioning
confidence: 99%
See 1 more Smart Citation